Crystallization of polymers from stressed melts - Kumaraswamy, Guruswamy (Journal of Macromolecular Science-Polymer Reviews, 2005)
In the last decade, there have been several investigations into the route by which a polymer melt that has been subjected to flow transforms into a crystalline state. Crystallization of polymers from flowing or stressed melts is a technologically important problem since most thermoplastics are subjected to intense flow fields during normal processing operations. The renewed interest in this problem is due to the availability of new experimental tools that, coupled with advances in modeling and simulations, are beginning to yield insights into the molecular characteristics that control the crystallization pathways adopted by a stressed polymer melt. Recent evidence conclusively implicates the high molecular weight tail in promoting crystallization on shearing. It appears that the formation of oriented nuclei in polydisperse melts is controlled by chain orientation of a small fraction of high molecular weight chains in a melt. Thus, it is the theological criteria for ``critical'' chain orientation that govern flow-induced acceleration and orientation in polymer crystallization. This review summarizes the literature on the effect of shearing on polymer crystallization, and focuses on recent advances in understanding the role of molecular parameters that couple polymer crystallization to flow and melt orientation.
Keywords: flow; polymer crystallization; processing; shear

Collapse transition in random copolymer solutions - Dasmahapatra, Ashok Kumar; Kumaraswamy, Guruswamy; Nanavati, Hemant (Macromolecules, 2006)
We present dynamic Monte Carlo lattice simulations of the coil to globule collapse of single chains of a copolymer comprising monomer units, m and c, wherein there is a net attractive interaction between c-units. As the copolymer is cooled, the solvent quality becomes poorer, and the size of the chain decreases, driven by the net m-m and c-c attractions. The strong c-c attraction increases the overall solvophobicity of the chain relative to a homopolymer and, therefore, copolymers collapse more abruptly and at a higher effective temperature relative to homopolymers. We compare copolymers with homopolymers by rescaling collapse data to the same theta values to account for the effect of overall solvophobicity. This comparison shows that the behavior of copolymers and the corresponding homopolymers is identical as the chain size reduces from high temperatures to the theta value. Beyond theta, copolymers with c-content < similar to 50% collapse more abruptly than either homopolymer, after accounting for the difference in overall solvophobicity. Collapse of copolymers containing higher c-content is dominated entirely by the c-c attractions, and these chains behave qualitatively like homopolymers with a higher effective solvophobicity. Analysis of the chain structure during collapse provides a structural reason for the qualitative change in copolymer collapse at low c-content. When such copolymers are cooled below theta, the c-units rapidly aggregate to form an isotropic, compact core surrounded by an anisotropic solvated shell of m-units. The shell densifies as the copolymer is further cooled, but remains anisotropic for the finite chain sizes investigated.

Composites of polypropylene with layered Mg-silsesquioxanes show an unusual combination of properties - Kumaraswamy, Guruswamy; Deshmukh, Yogesh S.; Agrawal, Vikrant V.; Nisal, Anuya (Industrial & Engineering Chemistry Research, 2008)
We report the synthesis of vinyl modified magnesium silsesqiuoxanes (''vinyl clay''), and the formation of their composites with isotactic polypropylene (iPP) by melt compounding. Vinyl clay is a layered compound with a layer thickness of approximately 1 nm. Vinyl clay does not exfoliate in iPP; rather, it disperses to form a network that exhibits a characteristic low frequency solid-like plateau in the elastic modulus in dynamic melt theological measurements. Strangely, vinyl clay also plasticizes iPP-there is a decrease in the high frequency complex viscosity. The decrease in the complex viscosity is higher at higher frequencies, suggesting the influence of slip at the iPP-vinyl clay interface. The combination of the low frequency elastic plateau and plasticization makes the vinyl clay composite significantly more shear thinning than the matrix iPP. In the solid state, vinyl clay-iPP composites exhibit increased tensile modulus (showing approximate to 50% increase for a 5% loading), but surprisingly, no corresponding decrease in the elongation at break. Thus, while microstructural characterization indicates that only a small fraction, if any, of the vinyl clay is exfoliafed, the enhancement in mechanical properties is similar to that observed for iPP-exfoliated montmonillonite nanocomposites. Our compounding protocol is unable to effectively disperse the clay in the iPP at clay loadings greater than about 7.5%. Therefore, the low frequency plateau in the melt elastic modulus and the solid tensile modulus increase with clay loading until 7.5% but exhibit a nonmonotonic decrease at higher clay loadings.

Compact polar moieties induce lipid-water systems to form discontinuous reverse micellar phase - Kumar, Manoj; Patil, Naganath G.; Choudhury, Chandan Kumar; Roy, Sudip; Ambade, Ashootosh V.; Kumaraswamy, Guruswamy (Soft Matter, 2015)
The role of molecular interactions in governing lipid mesophase organization is of fundamental interest and has technological implications. Herein, we describe an unusual pathway for monoolein/water reorganization from a bicontinuous mesophase to a discontinuous reverse micellar assembly, directed by the inclusion of polar macromolecules. This pathway is very different from those reported earlier, wherein the Fd3m phase formed only upon addition of apolar oils. Experiments and molecular dynamics simulations indicate that hydrophilic ternary additives capable of inducing discontinuous phase formation must (i) interact strongly with the monoolein head group and (ii) have a compact molecular architecture. We present a detailed investigation that contrasts a monoolein-water system containing polyamidoamine (PAMAM) dendrons with one containing their linear analogs. The Fd3m phase forms only on the addition of PAMAM dendrons but not their linear analogs. Thus, the dendritic architecture of PAMAM plays an important role in determining lipid mesophase behavior. Both dendrons and their linear analogs interact strongly with monoolein through their amine groups. However, while linear polymers adsorb and spread on monoolein, dendrons form aggregates that interact with the lipid. Dendrons induce formation of an intermediate reverse hexagonal phase, which subsequently restructures into the Fd3m phase. Finally, we demonstrate that other additives with compact structures that are known to interact with monoolein, such as branched polyethylenimine and polyhedral silsesquioxane cages, also induce the formation of the Fd3m phase.

Colloidal assembly by ice templating - Kumaraswamy, Guruswamy; Biswas, Bipul; Choudhury, Chandan Kumar (Faraday Discussions, 2016)
We investigate ice templating of aqueous dispersions of polymer coated colloids and crosslinkers, at particle concentrations far below that required to form percolated monoliths. Freezing the aqueous dispersions forces the particles into close proximity to form clusters, that are held together as the polymer chains coating the particles are crosslinked. We observe that, with an increase in the particle concentration from about 106 to 108 particles per ml, there is a transition from isolated single particles to increasingly larger clusters. In this concentration range, most of the colloidal clusters formed are linear or sheet like particle aggregates. Remarkably, the cluster size distribution for clusters smaller than about 30 particles, as well as the size distribution of linear clusters, is only weakly dependent on the dispersion concentration in the range that we investigate. We demonstrate that the main features of cluster formation are captured by kinetic simulations that do not consider hydrodynamics or instabilities at the growing ice front due to particle concentration gradients. Thus, clustering of colloidal particles by ice templating dilute dispersions appears to be governed only by particle exclusion by the growing ice crystals that leads to their accumulation at ice crystal boundaries.

Capillary uptake in macroporous compressible sponges - Chatterjee, Soumyajyoti; Doshi, Pankaj; Kumaraswamy, Guruswamy (Soft Matter, 2017)
The capillarity-driven uptake of liquid in swellable, highly porous sponges is of significant industrial importance. Sponges prepared using polymers and their composites with carbon nanotubes and graphene have been reported, with extraordinary solvent uptake capacities and with the ability to separate oil from water. However, the effect of systematic variation of sponge characteristics on solvent uptake has not been investigated. Here, we report experiments that study capillary uptake in a variety of flexible, centimetre-sized macroporous cylindrical sponges. We used ice-templating to prepare a series of model macroporous sponges in which the porosity, modulus and composition were systematically varied. We investigated two kinds of sponge: (a) those composed purely of cross-linked polymers and (b) those prepared as composites of inorganic particles and polymers. Both kinds of sponge are flexible and exhibit elastic recovery after large compressive deformation. All sponges were characterized thoroughly with respect to their pore microstructure and elastic modulus. When one end of a sponge is plunged into a large reservoir, water rises through capillary action against gravity. We observed a transition from an inertial capillary regime, where the liquid column height rose linearly with time, t, to a viscous capillary regime, where the liquid height rose with time t(0.5). We showed that these results can be rationalized using analyses developed for rigid sponges. We combined differential momentum balance equations for uptake in rigid capillaries with the phenomenological Ergun-Forchheimer relations to account for the effect of the sponge microstructure. This approach works remarkably well in the viscous capillary regime and shows that capillary uptake is governed primarily by the total porosity and pore dimensions of soft sponges.
Keywords: aerogels; Building blocks; Catalyst Supports; Contact-angels; Dynamics; flow; Organic Liquids; Porous-Media; Rise

Characterizing microvoids in regenerated cellulose fibers obtained from viscose and lyocell processes - Sharma, Aakash; Sen, Debasis; Thakre, Shirish; Kumaraswamy, Guruswamy (Macromolecules, 2019)
Regenerated cellulose fibers are among the most widely used bio-derived materials. Currently, there is great interest in transitioning from the traditional viscose process to the more environmentally friendly lyocell process for fiber production. Differences between the characteristics of viscose and lyocell fibers can be attributed to microstructural differences that arise due to differences in the processing techniques. Here, we use small-angle scattering to characterize the microvoids in regenerated cellulose fibers that might govern the onset of mechanical failure in these. In regenerated cellulose fibers, scattering of X-rays or neutrons at small angles is largely dominated by scattering from microvoids. We demonstrate that small angle X-ray scattering (SAXS) over the q range that is typical for most commercial instruments arises from Porod scattering from the microvoid surfaces, viz., the scattered intensity scales as q(-4). Therefore, it is not possible to extrapolate this data to lower q to obtain microvoid dimensions and volume fraction. We combine SAXS with medium-resolution small-angle neutron scattering to characterize the microvoids in regenerated cellulose fibers. Specifically, we compare fibers produced using the viscose process with those from the lyocell process. For both viscose and lyocell fibers, microvoids have a high aspect ratio and are elongated in the fiber direction. Also, the volume fraction occupied by the microvoids is comparable for viscose and lyocell fibers (0.04-0.05%). However, there are differences in the microvoid size: Microvoids are more highly oriented in lyocell fibers and have a larger average length and diameter compared with viscose fibers. This result might have important implications for understanding failure of these fibers.

Critical role of processing on the mechanical properties of cross-linked highly loaded nanocomposites - Suresh, Karthika; Chowdhury, Arindam; Kumar, Sanat K.; Kumaraswamy, Guruswamy (Macromolecules, 2019)
Polymer nanocomposites are frequently not at equilibrium-therefore, the structure and properties critically depend on the protocol followed in their preparation. Here, we demonstrate that the elastic-brittle transition in highly loaded ice-templated polymer nanocomposites is sensitively determined by the conformation of polymer chains during nanocomposite preparation. Macroporous polymer nanocomposites are synthesized using two preparation pathways, both exhibiting minor modifications of the ice-templating method wherein an aqueous dispersion of nanoparticles, polymers, and cross-linkers is frozen. In one method, the matrix polymer is cross-linked in the presence of ice, whereas in the other method, the ice is removed by freeze-drying before the polymer is cross-linked. Although all measurable structural metrics are practically identical for the two composites, they exhibit qualitatively different mechanical properties. Nanocomposites cross-linked in the presence of ice show exceptional resilience, recovering elastically from large compression for very high nanoparticle loadings-in some instances, above 90% by weight. Here, the critical particle loading for the elastic- brittle transition is dependent on the molecular weight of the polymer. In comparison, samples cross-linked after freeze-drying appear structurally identical but turn brittle at much lower particle loadings (about 60% by weight), independent of the matrix polymer molecular weight. We rationalize these differences in terms of the conformational state of the polymer during cross- linking. In the former case, polymer chains are in good solvent during nanocomposite preparation, while after lyophilization, they are in a poor solvent. The large spatial extent of well-solvated chains and chain-chain overlap during cross-linking results in the formation of intermolecular cross-links, and we obtain elastic nanocomposites even at high nanoparticle loadings. In contrast, for chains in collapsed conformations in a bad solvent, chain connectivity during cross-linking is achieved only for much lower particle loadings. Our results reiterate that the sensitivity of polymer conformations to different processing methods can result in large differences in properties, even though their consequences on structural characteristics are effectively indistinguishable.

Colloidal assembly by directional ice templating - Biswas, Bipul; Misra, Mayank; Bisht, Anil Singh; Kumar, Sanat K.; Kumaraswamy, Guruswamy (Soft Matter, 2021)
We investigate directional ice templating of dilute aqueous colloidal particle dispersions and examine the nature of the assemblies that result. We coat micron-size polystyrene colloids with cross-linkable polymer (polyethyleneimine, PEI), add cross-linker, and subject this dispersion to unidirectional freezing. We work at sufficiently low colloid concentrations, such that the particles do not percolate on freezing. When the aqueous dispersion freezes, ice crystals force polymer-coated particles and cross-linker into close proximity. This results in the formation of cross-linked clusters of particles at ice crystal boundaries. We vary the particle volume fraction from phi similar to 2.5 x 10(-3) to phi similar to 5.0 x 10(-2) and observe that there is a transition from isolated single particles to increasingly large sized clusters. Most of the clusters formed under these conditions are either linear, two-particle wide chains, or sheet-like aggregates. The probability (P-n) of clusters containing n particles (n > 2) obeys a power law P-n similar to n(-eta), where eta strongly depends on the particle concentration in the dispersion, varying from 2.10 (for phi similar to 5.0 x 10(-2)) to 3.03 (for phi similar to 2.5 x 10(-3)). This change in eta is qualitatively different from the case of isotropic freezing, where eta is particle concentration-independent and depends only on the ice nucleation density. To understand the differences between isotropic and directional ice templating, we performed lattice simulations of a highly simplified model, where ice crystals grow at a constant rate to force clustering. We ignore hydrodynamic interactions and ice growth instabilities. Despite ignoring these experimental details, the simulations capture the experimental results, nearly quantitatively. As the ice crystals grow and the space available to the colloids ``closes up'' so that the particles cluster to form aggregates, crystallization protocol-induced differences in the geometry of these ``closed up'' spaces determine the scaling behaviour of P-n.